Classic And Network Epidemiological Models - Christian Camilo Cortes Garcia (Scientia Et Technica, 2021)
In this work is analyzed the environment and the dynamics of the states for a disease within a constant and closed population, represented by a system of ordinary differential equations, in which the individual, besides having the same opportunity to get in contact with any other, can recover or not, acquiring or not immunity through time. With these defined guidelines, the conditions when the disease spreads over time between such models are compared with those represented by a network. As the network can be represented by an adjacency matrix, the dynamics in the epidemiological states depends, besides the conditions in their parameters of the classic models, on largest eigenvalueof such matrix.